Human Resource Management Strategy to Improve the Quality of Education: Leadership and Organizational Perspectives - Farhani, Ashfiya Tri; Febriana, Kurnia Rizki; Sukainah, Siti (UM Purwokerto Press, 2025)
Improving the quality of education is a strategic agenda in the development of sustainable human resources. One of the key factors determining the success of education is the effectiveness of human resource management (HRM), particularly in the context of leadership and organizational dynamics. This article aims to explore HRM strategies within the framework of improving educational quality through a literature review of leadership, organizational, and educational management theories. This theoretical approach emphasizes that successful HRM is significantly influenced by visionary, participatory, and transformational leadership styles, as well as adaptive, collaborative, and performance-based organizational structures. The strategies reviewed include competency-based recruitment, continuous professional development, fair incentive systems, and the creation of a work culture that supports innovation and collaboration. In addition, the integration of organizational policy and leadership in supporting the development of teachers and educational staff is identified as a crucial aspect in building high-quality educational institutions. The method used in this article is qualitative descriptive, with data collected through literature reviews by gathering documents such as books, journal articles, and relevant thematic materials. This article proposes that the synergy between HRM strategies, effective leadership, and sound organizational governance forms the foundation for sustainably enhancing educational quality. The findings of this study are expected to serve as a conceptual basis for policymakers, school leaders, and researchers in designing HRM models that are aligned with the challenges and needs of 21st-century education.